Characterisation of N‐(Octadecyl)‐1, 8‐naphthalimide Monolayer Compression Using Molecular Dynamics and Experimental Approaches. Issue 8 (21st January 2019) - Welsh, Ivan D.; Draper, Daria; Kim, Jaehwan; Kitchen, Jonathan A.; Allison, Jane R.
Abstract: The development of luminescent surfaces is an active area of supramolecular chemistry, particularly for the development of new sensing platforms. One particularly useful surface deposition method is the Langmuir–Blodgett technique where organic amphiphilic fluorophores (e.g. 1, 8‐naphthalimides) can form ordered monolayers at an air–water interface before being deposited onto solid supports. The ability to simulate monolayer formation and consequently develop predictability over film formation would allow for significant advances in the luminescent materials field where synthesis might be directed by simulation data. Here, we compare pressure‐area isotherms of N ‐(octadecyl)‐1, 8‐naphthalimide determined experimentally, using the Langmuir–Blodgett technique, and computationally, using three different simulation techniques. We find that all three simulation techniques are able to describe the liquid‐condensed/liquid‐expanded region of the isotherm, and that the isotherms are highly similar in this region, although the NγT ensemble performs best. Experimental isotherms showed film formation properties that align with the simulation data, suggesting that simulations are a viable means to direct synthesis. Investigation of the underlying structural details disclosed by the simulations reveals the compression‐induced ordering at atomic‐level detail, which will allow prediction of how functionalisation of the naphthalimides will alter the monolayer compression and mounting process. Abstract : The Langmuir–Blodgett technique allows surface deposition of organic amphiphilic fluorophores and is thus useful for the development of new sensing platforms comprising luminescent surfaces. Comparison of pressure‐area isotherms of N ‐(octadecyl)‐1, 8‐naphthalimide determined experimentally and computationally showed that simulation and experiment align, suggesting that simulations are a viable means to direct synthesis. Moreover, the simulations reveal the compression‐induced ordering at atomic‐level detail, which will allow prediction of how functionalisation of naphthalimides and other molecules will alter the surface formation process.